Personalisasi Nilai Pelanggan dalam Pemasaran Digital: A Systematic Literature Review Perspective from Customer Value Theory - Dassucik, Dassucik; Rasyidi, Ahmad Hafas; Mujanah, Siti; Halik, Abdul; Azizah, Nur (Universitas Hamzanwadi, 2025)
Digital marketing has evolved rapidly with advancements in technologies such as artificial intelligence (AI), big data analytics, and machine learning. One of the main innovations in digital marketing is personalization, which refers to tailoring messages, offers, and customer experiences based on individual preferences, behaviors, and past interactions with brands. This study aims to analyze how personalization in digital marketing influences customer perceived value, using the Customer Value Theory as the analytical framework. Through a Systematic Literature Review (SLR), this research identifies the relationship between personalization and customer value across functional, emotional, and social dimensions, as well as how it impacts customer loyalty and brand equity. The study also highlights challenges related to the ethical use of data and the long-term impact of personalization on customer loyalty. Based on these findings, further research is needed to explore variations in responses to personalization influenced by culture and demographics, and to examine the role of new technologies like AI, AR (augmented reality), and blockchain in enhancing customer experiences.